Study on the numerical analysis of storm surges around the coastal zone of Bangladesh - Joty, Musarrat Rashidi (Brac University, 2024)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Mathematics 2023.